HUBUNGAN PENGETAHUAN DAN PERUBAHAN FISIK WANITA PREMENOPAUSE DENGAN KECEMASAN WANITA MENOPAUSE - Bela Purnama Dewi; Rakhma Syahera (LPPM STIKes Mitra Adiguna, 2024)
Increasing the age of marriage is a program from the National Population and Family Planning Agency (BKKBN) which seeks to increase the age of first marriage for men and women to a minimum of 19 years. The aim of this research is to determine the effect of providing educational videos in increasing knowledge about maturing marriage age among teenagers. Research uses design pre experiment with pre and post test design with control group. Instruments used in the research include : knowledge questionnaires about maturing marriage age, educational videos, leaflet, and powerpoint made by the researcher himself. Technique sampling which is used is purposive sampling. Analysis using test Wilcoxon with the results of the analysis showing that there is a significant influence or difference in the increase in the average value of knowledge about maturation at marriage between before and after the intervention (p-value = 0.00). Providing educational videos can increase respondents’ knowledge about maturing marriage age.